Paeoniflorin Inhibits Mesangial Cell Proliferation and Inflammatory Response in Rats With Mesangial Proliferative Glomerulonephritis Through PI3K/AKT/GSK-3β Pathway - Liu, Bihao; Lin, Jin; Bai, Lixia; Zhou, Yuan; Lu, Ruirui; Zhang, Peichun; Chen, Dandan; Li, Honglian; Song, Jianping; Liu, Xusheng; Wu, Yifan; Wu, Junbiao; et al. (Frontiers in Pharmacology, 2019)
Mesangial proliferative glomerulonephritis (MsPGN) is the most common type of chronic kidney diseases in China, characterized by mesangial cells proliferation and inflammatory response. Paeoniflorin, an effective composition extracted from Radix Paeoniae Alba, has been used for various kinds of kidney diseases for many years. However, there are no studies reporting the effects of paeoniflorin on MsPGN. The present study is aimed to investigate whether paeoniflorin plays a role in MsPGN and confirm the underlying molecular mechanisms. Our results manifest that paeoniflorin strongly promoted renal function, restrained 24 h urinary protein and dyslipidemia in a MsPGN rat model. Moreover, paeoniflorin attenuates mesangial cells proliferation and inflammation both in MsPGN rats and human mesangial cells (HMCs) treated with lipopolysaccharide (LPS). In detail, paeoniflorin decreased the numbers of mesangial cells and expressions of proliferation marker Ki67 in MsPGN rats. Paeoniflorin also inhibited HMCs proliferation and blocked cell cycle progression. In addition, the contents of inflammatory factors and the expressions of macrophage marker CD68 were decreased after paeoniflorin treatment. Furthermore, we found that the protective effect of paeoniflorin is accompanied by a strong inhibition of phosphatidylinositol 3-kinase (PI3K)/AKT/glycogen synthase kinase (GSK)-3β pathway, which is enhanced by PI3K inhibitor LY294002, and suppressed by PI3K agonist insulin-like growth factor 1 (IGF-1). In conclusion, these results demonstrate that paeoniflorin ameliorated MsPGN by inhibiting mesangial cells proliferation and inflammatory response through PI3K/AKT/GSK-3β pathway.